Needs Analysis for the Development of a Project-Based Learning–Based E-Module on Virus Topics as Teaching Material for Grade X (Phase E) Senior High School Students - Tutik Ari Murti; Harlita Harlita; Puguh Karyanto (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2026)
Virus materials are inherently abstract and present considerable challenges for Grade X (Phase E) senior high school students when taught using conventional instructional methods. Therefore, effective instruction on virus concepts requires innovative teaching materials that facilitate conceptual understanding and promote active learning. One promising medium is an electronic module (e-module). Accordingly, this study aimed to conduct a needs analysis for developing a Project-Based Learning (PjBL)-based e-module on virus topics as instructional material. The study used a descriptive, quantitative design to examine the need to develop the proposed e-module. The analysis investigated current learning practices, students’ learning experiences, perceptions of e-modules, and the need for a virus e-module integrated with the PjBL model. Participants included 33 students and 15 biology teachers. Data were collected through questionnaires distributed via Google Forms and analyzed using descriptive quantitative techniques. Results showed that 97% of students experienced difficulties understanding virus material. Furthermore, all students (100%) reported the need for additional learning resources and preferred e-modules containing visual representations, instructional videos, and interactive exercises. Most students also favored resources that were accessible anytime, anywhere via digital devices. Teachers likewise emphasized the need for e-modules that provide clearly structured project stages, contextual case studies, and standardized project report formats to support PjBL implementation. These findings indicate that developing a PjBL-based e-module is essential to enhance biology learning effectiveness, support independent learning, and help students develop competencies aligned with modern educational demands in secondary education contexts, and strengthen engagement with complex biological concepts through project activities and reflection.